Students’ Strategies in English Learning at Home During the Covid-19 Pandemic - Ruslan Hasyim; Rizal Akib; Erikson Penggu; Jusriati; Nahdawati Nahdawati (ITScience (Information Technology and Science), 2022)
English is an international language, and there are many people or students in the world learning English. All the students have different abilities or strategies for learning English. Without a plan and the students cannot improve their English skills well. So when the students want to learn English should have a strategy because it is will helpful. This research is to determine the method and obstacles English students face in learning English at home during the COVID-19 pandemic at students' universities. This is descriptive, using a qualitative approach with data collection techniques using interviews. The sample in this study was 5 participants from the English Department in the 7th semester of the academic year 2020./2021. The researcher found that of the five participants, the most widely used strategy by students was the first social strategy; most of them practiced English with their parents, family, or friends at home during the pandemic. The second is a compensation strategy; in this strategy, students learn English by listening to songs or reading books to improve their vocabulary. The third is a memory strategy; in this strategy, students learn by listening to songs, radio, or watching on youtube instead of taking vocabulary notes, and they memorize them during the pandemic. Constraints faced by students when learning English at home during the pandemic. Many obstacles faced by students, namely lack of money, not being able to buy internet quota, laziness to move because of the pandemic, unable to accept and laziness to take all the courses given by lecturers, and not having learning tools such as laptops, English dictionaries to help them learn English at University.